Robust hybrid anti-islanding method for inverter-based distributed generation - Abdolrasol, M.G.M.; Mekhilef, Saad (2010)
This paper proposes a robust hybrid anti-islanding method for Inverter-based Distributed Generation (DG). This method is based on Active and passive detection techniques. Active anti islanding technique generates disturbances at the output of the distributed generation by Positive feedback and Continuous feedback signal injection which is based on DQ implementation. On the other hand passive anti islanding technique detects islanding by measuring voltage, frequency, active and reactive power and total harmonic distortion (THD). This technique uses resistive, capacitive and inductive connected in parallel RLC load and compares the performance of the technique with and without the controller. This method of control is shown to be robust, able to detect islanding under different types of loads, and fast in response. Possible islanding conditions are simulated and verified with full analysis.